BIBIONA ARXEOLOGIK YODGORLIGINI O‘RGANILISH TARIXI - Bekmirzayev , Islomjon Ibrohim o‘g‘li (Innovative Development in Educational Activities, 2022)
This article presents the archaeological researches and their achievements in the settlement of Bibiona, which is located on the banks of the Chust stream, in the middle course of the Govasoy, located in the Northern Fergana valley. Also, it was emphasized that the archaeological researches, which started in 1950 and are still ongoing, and their results are a valuable monument in restoring the archeology and history of Uzbekistan, and the period of archaeological research was divided into 3 stages by the author.